Postcolonial writers in the global literary marketplace - Brouillette, Sarah, 1977- (Palgrave Macmillan, 2007)
"Postcolonial Writers in the Global Literary Marketplace considers some of the market conditions that have framed the emergence of English-language postcolonial literatures, and suggests modifications to existing accounts of how a writer's marginality is experienced by consumers of postcolonial texts. Arguing that the incorporation of writers who are marketed as postcolonial has been crucial to global expansion and consolidation in the publishing industry, Sarah Brouillette connects market incorporation to the self-consciousness of a set of postcolonial writers. She situates their attempts at self-definition, self-critique, and self-defence within the general history of literary authorship, and argues for new ways of understanding authorship in light of the experiences of figures like Derek Walcott and Salman Rushdie. Combining explorations of existing theory with wide-scale market analysis and close attention to writers' careers and texts, this study makes an exciting contribution to globalization studies and to the emerging history of the postcolonial book"--Publisher's description.